2019
DOI: 10.1001/jamacardio.2019.4032
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cardiac Rehabilitation With Decreased Hospitalization and Mortality Risk After Cardiac Valve Surgery

Abstract: IMPORTANCE National guidelines recommend cardiac rehabilitation (CR) after cardiac valve surgery, and CR is covered by Medicare for this indication. However, few data exist regarding current CR enrollment after valve surgery.OBJECTIVE To characterize CR enrollment after cardiac valve surgery and its association with outcomes, including hospitalizations and mortality. DESIGN, SETTING, AND PARTICIPANTS This cohort study of patients undergoing valve surgery was conducted in calendar year 2014, with follow-up thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 28 publications
3
47
0
7
Order By: Relevance
“…Centre-based CR for individuals who have experienced a cardiovascular hospitalization or undergone a cardiovascular procedure is associated with improved survival and lower rates of rehospitalization. 6 , 7 Indeed, the magnitude of the benefit that comes from participation in CR exceeds many expensive drugs and procedures in medicine. For example, a recent analysis of Medicare patients undergoing cardiac valve surgery showed that CR participation was associated with a 61% relative decrease and 4.2% absolute decrease in 1-year mortality risk and a 34% reduction in the relative risk of rehospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Centre-based CR for individuals who have experienced a cardiovascular hospitalization or undergone a cardiovascular procedure is associated with improved survival and lower rates of rehospitalization. 6 , 7 Indeed, the magnitude of the benefit that comes from participation in CR exceeds many expensive drugs and procedures in medicine. For example, a recent analysis of Medicare patients undergoing cardiac valve surgery showed that CR participation was associated with a 61% relative decrease and 4.2% absolute decrease in 1-year mortality risk and a 34% reduction in the relative risk of rehospitalization.…”
Section: Discussionmentioning
confidence: 99%
“… 5 A recent report on cardiac rehabilitation (CR) after valve surgery showed that although CR was associated with reduced rehospitalization and mortality in the first year after the surgery, participation rates were only 43%. 6 While the literature demonstrates similar associations between CR and reduced mortality among patients treated for coronary artery disease, rates of participation are even lower. 7 , 8 Participation in CR after TAVR has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Sufficient evidence-based data on adverse events, mortality, quality of life, symptoms and reversible left ventricular remodeling are not yet available [5]. A recently published large American cohort study demonstrated CR participation to be associated with reduction in hospital admissions and mortality rate within the first year after CR completion [8]. However, there are no generally accepted and evaluated standards for the content, mode, volume, and intensity of exercise-based CR after valve surgery or intervention [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Die Reduktion der Mortalität war gleich zwischen den Gruppen mit/ohne begleitende ACB-Op. und unabhängig davon, ob die KardReha sofort nach Operation oder erst später begonnen wurde [7].…”
Section: Der Kardiologe 2 · 2020 109unclassified